The Relationship Between Self-Regulated Learning and Academic Stress During Online Learning for University Students: Hubungan Antara Self Regulated Learning dengan Stres Akademik Saat Pembelajaran Daring pada Mahasiswa di Universitas - Dian Putri Linayanti; Nurfi Laili (Academia Open, 2022)
This study aims to determine the relationship between Self Regulated Learning and Academic Stress During Online Learning in Psychology Study Program Students, University of Muhammadiyah Sidoarjo. The variables contained in this study are self-regulated learning as the independent variable and academic stress as the dependent variable. This research uses non - probability sampling technique . The number of samples used were 248 students. The results in this study indicate a correlation coefficient of -0.466 with a significance value of 0.000 <0.05, it can be concluded that there is a negative relationship between self-regulated learning and academic stress. This means that the higher self-regulated learning during online learning, the lower academic stress during online learning experienced by psychology study program students at Muhammadiyah University of Sidoarjo, on the other hand, if self-regulated learning is lower, academic stress during online learning will be higher. Highlights: Negative correlation: The study found a negative relationship between self-regulated learning and academic stress during online learning among psychology study program students. Higher self-regulated learning was associated with lower academic stress. Sample size and technique: The research utilized a non-probability sampling technique and included a sample of 248 students, emphasizing the generalizability of the findings to the target population. Significance of online learning: The study specifically focused on the context of online learning, highlighting the importance of self-regulated learning in mitigating academic stress among students in the psychology study program at the University of Muhammadiyah Sidoarjo. Keywords: Self-regulated learning, academic stress, college students, online learning, psychology study program